Non-Polluting Chemical Approaches to Control Citrus Postharvest Diseases - Palou, Lluís (MedCrave, 2022)
Commercial cultivars of Citrus spp. (Rutaceae), including oranges, mandarins or tangerines, grapefruits, lemons, and limes are the most widely produced fruits in the world. China, Brazil, and the United States (USA) lead the global production, which is mainly devoted to juice extraction, but Spain is the leading country for exports of fresh entire fruit for direct consumption. Among postharvest losses of fresh fruit, those of pathological origin are especially important because whole export shipments are often rejected by wholesale buyers when they find rotten fruits, even at low proportions. In these cases, the producer is also charged for the transport and handling costs [1].